Structural relationship between learners' perceptions of a test, learning practices, and learning outcomes: A study on the washback mechanism of a high-stakes test. (March 2020) - Dong, Manxia
Highlights: Learners' perceptions of test affected learning practices in different ways. Learners' perceptions of test affected learning practices to varying degrees. Learning practices positively and significantly affected learning outcomes. Learning practices have differential effects on learning outcomes. Effect size of learning practices on outcomes relates to participation frequency. Abstract: The study aimed to explore the washback mechanism on learning by investigating the structural relationship between learners' perceptions of a test, learning practices, and learning outcomes via structural equation modeling. The participants in this study included 3105 Chinese senior high school students. Exploratory factor analysis, confirmatory factor analysis, and structural equation modeling were used in the analyses of the data. This study found that learners' perceptions of test validity, impact, and importance affected their learning practices in different ways and to different degrees. The research results also showed that four types of English learning practices had significant, positive, but differential effects on learning outcomes. The effect size was partly associated with the frequency of engagement with each learning practice. Based on the findings, some implications and suggestions were drawn for learners, teachers, test designers, and test authorities.